A Study on the Use of the Cambridge Curriculum in English Class at SMP Islam As-Shofa Pekanbaru - Bunaya Aziz, Thariqh; Erni; Harfal, Zaldi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research uses a qualitative method with a narrative type, which has the purpose to find out how SMP Islam As-Shofa Pekanbaru in using the Cambridge Curriculum. Specifically, this research answers research questions about how SMP Islam As-Shofa Pekanbaru uses the Cambridge curriculum and explains the challenges during the implementation of the Cambridge curriculum in English subjects at SMP Islam As-Shofa Pekanbaru. This research uses interviews and documentation as data collection techniques. The principal, deputy curriculum coordinator, and six English teachers at SMP Islam As-Shofa Pekanbaru became informants who were interviewed by researchers as primary data. Documentation was subsequently used as supporting data for this research. The results showed that the use of the Cambridge curriculum at As-Shofa Islamic Junior High School Pekanbaru could be said limited in the use of Cambridge curriculum classroom tools in which As-Shofa Islamic Junior High School can access it all because it collaborates with Mentari as the publisher. The use of classroom tools from Cambridge Curriculum in this school is supported by the style of togetherness between English teachers who always discuss together English learning and also the form of supervision carried out by the Foundation and the school that runs smoothly. In addition, teachers still have difficulties in implementing this curriculum. The difficulty is in the form of differences in the background of students' ability to use English. Another difficulty also comes from the British accent used in books and media from the Cambridge curriculum makes teachers more ingenious to be able to convey the material taught so that it can be understood well by students.